Cognitive impairment, perceived medication adherence, and high‐risk medication use in patients with reduced kidney function: A cross‐sectional analysis. Issue 4 (29th June 2022) - Sheets, Kerry M.; Davey, Cynthia S.; St. Peter, Wendy L.; Reule, Scott A.; Murray, Anne M.
Abstract: Background and Aims: Reduced estimated glomerular filtration rate (eGFR < 60 ml/min/1.73 m 2 ) is a risk factor for cognitive impairment (CI) and medication nonadherence. However, the association between CI and medication adherence in adults with reduced eGFR has not been adequately examined. Our pragmatic objectives were to assess the cross‐sectional relationship between CI and self‐reported medication adherence, medication number, and use of potentially high‐risk medications among adults with reduced eGFR. Methods: An observational cohort study of the epidemiology of CI in community‐dwelling adults aged 45 years or older with reduced eGFR. Results: Our analytic cohort consisted of 420 participants (202 with CI; mean age: 69.7 years) with reduced eGFR, at least one prescription medication, and nonmissing medication adherence data. Participants with CI had four times greater unadjusted odds of reporting good medication adherence than participants without CI (self‐report of missing medications <4 days/month; odds ratio [OR]: 4.04, 95% confidence interval [CI]:​​​​​ 1.62–10.10). This difference persisted following adjustment for demographic factors and comorbidities (OR: 5.50, 95% CI: 1.86–16.28). Participants with CI were no more likely than participants without CI to report forgetfulness as a reason for missing medication doses. Participants with CI were, on average, taking more total (mean: 13.3 vs. 11.5, median: 12 vs. 11) and more high‐risk (mean: 5.0 vs. 4.2, median: 5 vs. 4) medications than those without CI; these differences were attenuated and no longer significant following adjustment for demographics and comorbidities. Conclusion: Given the well‐documented association between CI and medication nonadherence, better self‐reported medication adherence among those with CI may represent perceptions of adherence rather than actual adherence. Participants with CI were, on average, taking more total and more high‐risk medications than those without CI, suggesting a possible increased risk for adverse drug events. Our results highlight the potential risks of relying on self‐reported medication adherence in reduced eGFR patients with CI.